Delayed luminescence induced by complex domains in water and in TEOS aqueous solutions. Issue 2 (2nd December 2015) - Colleoni, C.; Esposito, S.; Grasso, R.; Gulino, M.; Musumeci, F.; Romeli, D.; Rosace, G.; Salesi, G.; Scordino, A.
Abstract : Many recent studies on water have conjectured a complex structure composed of hydrogen bonded low- and high-density domains. Abstract : Many recent studies on water have conjectured a complex structure composed of hydrogen bonded low- and high-density domains. In this work the structure of pure water and aqueous solutions of silica gel (TEOS) has been investigated by using delayed luminescence, which has previously shown a significant increase in aqueous salt solutions where low-density domain formation is expected. Photon emission shows an Arrhenius trend with an activation energy in water–TEOS solutions larger than in pure water and salt-water solutions. Moreover, delayed photon emission decay shows an intrinsic lifetime of about 5 μs both in solutions and in pure water that, along with secondary lifetimes induced by the presence of TEOS, could be related to the formation of different domains.